Integration of Electronic Business on Tourism: A Bibliometric Network Analysis - MAULANA, Yogi Sugiarto; MAULINA, Erna; KOSTINI, Nenden; HERAWATI, Tetty (Journal of Environmental Management and Tourism; Vol 13 No 6 (2022): JEMT, Volume XIII, Issue 6(62), Fall 2022, 2022)
This paper aims to map the position of electronic business tourism research and how these topics are related to one another. The bibliometric analysis method with VOSviewer is used to provide our understanding of the structure related to the topic under study, as well as to map and identify certain patterns, including analyzing and visualizing the co-occurrence of keywords, co-citations of cited authors, and co-citations of cited sources. A total of 117 documents on e-business and tourism topics from the Scopus database are reviewed. We find that the trend of research on e-business and tourism simultaneously has not increased significantly since 2003. We also found research topics that have the opportunity to be researched based on emerging keywords. In addition, we found the authors and journals who contributed the most to the topic of e-business and tourism research, and how they were connected. To our knowledge, this study is the first to conduct a bibliometric analysis on the topic of e-business and tourism simultaneously, in which 117 publications were systematically examined using bibliometric analysis with VOSviewer.